Diphenyl diselenide dietary supplementation protects against fumonisin B1-induced oxidative stress in brains of the silver catfish Rhamdia quelen - Baldissera M.D. (2020)
© 2020The trend toward using plant-based ingredients in aquafeeds has raised important concerns for aquaculture owing to the negative impacts of mycotoxins on fish health; with emphasis for contamination by fumonisin B1 (FB1). The brain is an important target of FB1; however, study of the pathways linked to brain damage is limited to an analysis of histopathological alterations. Reports have demonstrated the protective effects of dietary supplementation with diphenyl diselenide (Ph2Se2) in the brains of fish subjected to several environmental insults; nevertheless, its neuroprotective effects in fish fed with diets contaminated with FB1 remain unknown. Therefore, the aim of this study was to evaluate whether oxidative damage may be a pathway associated with FB1-induced neurotoxicity, as well as to evaluate whether dietary supplementation with Ph2Se2 prevents or reduces FB1-mediated brain oxidative damage in silver catfish. Brain reactive oxygen species (ROS), lipid peroxidation (LOOH) and protein carbonylation increased on day 30 post-feeding in animals that received FB1-contaminated diets compared to the control group, while brain antioxidant capacity against peroxyl radicals (ACAP) levels and catalase (CAT), glutathione peroxidase (GPx) and glutathione S-transferase (GST) activities were lower. Diphenyl diselenide dietary supplementation avoid increases in brain ROS levels, as well minimizing the augmentation of LOOH levels. Furthermore, Ph2Se2 prevented impairment of brain ACAP levels, as well as GPx and GST activities elicited by FB1-contaminated diets. These data suggest that dietary supplementation with 3 mg/kg Ph2Se2 prevented FB1-induced brain damage in silver catfish, and this protective effect occurred through avoided of excessive ROS production, as well as via prevention of brain lipid damage. Furthermore, Ph2Se2 exerted its neuroprotective effects via ameliorative effects on the enzymatic and non-enzymatic antioxidant defense systems, and may be an approach to prevent FB1-induced brain oxidative stress; however, is not an alternative to prevent the impairment on performance caused by FB1.